PROJECT PLANNING DIVERSION TUNNEL BAGONG DAM PROJECT TRENGGALEK REGENCY - Vidi Az Zahra; Fadjar Purnomo; Indah Ria Riskiyah (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
On the progress of construction development, especially in the construction of water buildings, one of which is a dam. In Trenggalek Regency a dam was built which was named Bagong Dam. This dam was built to control floods that commonly occur in the area. In the dam construction project there is a diversion tunnel building that is used to divert water flow during the main dam construction period. There were delays in the construction of this evasive building. The tunnel is a limited space, the difficulty of access roads, and equipment damage in some activities cause delays in the project so that it requires proper and efficient project planning. To complete this project, good cost, time, and quality considerations are needed so that it can be realized properly. This project planning aims to plan the organizational structure, strategies and methods, site layout preparation assisted using autocad application and Microsoft excel, quality plan, K3 plan, implementation budget plan, and scheduling using Microsoft Project 2021 application. Pure organizational structure planning is more efficient. By using a comparison of the use of existing and precast, it is found that the use of precast has a faster implementation duration of 180 days while if using the existing for 259 days. In the calculation of the implementation budget plan in precast amounting to Rp170,021,748,985 and in the existing obtained at Rp188,495,961,368. With these results, it is found that the use of precast is cheaper and more effective in the process. Quality planning is carried out according to the quality targets that have been made so that the building is according to plan. OHS planning is carried out to achieve Zero Accident. Effective site layout preparation is carried out for work efficiency.